2003
DOI: 10.3136/fstr.9.128
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Tea Catechins: Chemical Structures and Reaction Mechanism

Abstract: Black tea accounts for almost 80% of the world's tea production and is the most important source of polyphenol in the world. However, little has been known about the chemistry of black tea polyphenols due to their complexity. Since most of the black tea polyphenols are produced by enzymatic oxidation of green tea catechins, in vitro model fermentation experiments using purified catechins are very useful, and recently structures of some novel oxidation products of theaflavins, black tea pigments, have been eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 40 publications
4
70
1
10
Order By: Relevance
“…2008). Os chás produzidos a partir da planta Camellia sinensis são classificados em três categorias conforme o processo de fabricação: fermentado (preto), o semi-fermentado (oolong) e não-fermentado (verde) (Tanaka & Kouno, 2003;Soares, 2002;Matsubara & Rodriguez-Amaya, 2006a).…”
unclassified
“…2008). Os chás produzidos a partir da planta Camellia sinensis são classificados em três categorias conforme o processo de fabricação: fermentado (preto), o semi-fermentado (oolong) e não-fermentado (verde) (Tanaka & Kouno, 2003;Soares, 2002;Matsubara & Rodriguez-Amaya, 2006a).…”
unclassified
“…As loss of compartmentalization of (-)-epicatechin and anthocyanins with polyphenol oxidase (PPO) or peroxidase (POD) initiates the enzyme-catalyzed oxidation in the presence of oxygen, the oxidative products can further react with proteins or lipids and then form the brown-colored by-products [20]. Moreover, the formation of browning color of tea exhibited a similar reaction of quinines with proteins and lipids [21,22]. Thus, it is suggested that lipofuscin-like substance could be the final brown polymeric pigment from browning reaction of litchi fruit during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Drinks containing catechins also tend to contain acidic additives, such as water-soluble organic acids, with the most common acidifier being citric acid. The stability of tea catechins in aqueous solution has been investigated by many researchers (Chen et al, 1998;Friedman and Jürgens, 2000;Tanaka and Kouno, 2003). More recently, Aoshima and Ayabe studied methods to prevent the deterioration of catechin-enriched green tea (Aoshima and Ayabe, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the effects of the coexistence of octanoyl ascorbate, which is one of the most soluble acyl ascorbates in water, and citric acid on the degradation of catechin was compared with the case of ascorbic acid. (+)-Catechin solution, not green tea extracts, was selected as a simple system to investigate this, as complex reactions, such as the intermolecular coupled-oxidation between catechol ring and hydroxy o-quinone of catechins, may occur for solutions with mixed catechins (Tanaka and Kouno, 2003). …”
mentioning
confidence: 99%